Home advantage in elite soccer matches. A transient effect? - Lago-Penas, C.; Gomez, M. A.; Pollard, R. (International Journal of Performance Analysis in Sport, 2017)
The aim of the current study was to identify how the performances of home and away teams evolve during the first half of matches and to investigate whether or not the home advantage effect disappears or weakens as the game goes on. The sample consisted of 90 matches during the season 2015/2016 from the English FA Premier League (n = 19), French Ligue 1 (n = 21), Spanish La Liga (n = 18), Italian Serie A (n = 19) and German Bundesliga (n = 13) in which the first half ended with a score of 0-0. Data were examined using the autocorrelation function and linear regression analysis. Ball possession (p < .01), successful passes (p < .05), short passes (p < .01) and touches (p < .01) achieved their greatest values in the 0-5 min period compared with other match periods. However, as the first half went on, the home teams exhibited lower performances compared with those shown at the beginning of the match. This was particularly evident from the 16-20 min period until the end of the first half. This transient effect was enhanced or attenuated, depending on the quality of the opponent (p < .01). The better the opponent the lower the home teams` performances at the beginning of the match. These variables can be used to develop a model to simulate team performance of home and away teams during the first half of a match.